If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + -1m + 4m + 1 = 0 Reorder the terms: 1 + m + -1m + 4m = 0 Combine like terms: m + -1m = 0 1 + 0 + 4m = 0 1 + 4m = 0 Solving 1 + 4m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 4m = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 4m = 0 + -1 4m = 0 + -1 Combine like terms: 0 + -1 = -1 4m = -1 Divide each side by '4'. m = -0.25 Simplifying m = -0.25
| a=500(1+.06/2)*2 | | 3/8x-1/3+6 | | 3x-7=3(x+6) | | a=500(1+.06/2)2 | | C=8x+75 | | 9/3*(24/8) | | 16x-8-2=20 | | 9/3(24/8) | | 225-725x= | | 27/45 | | -35m-15=69 | | z^4+5iz^2+8=0 | | -4m-15=51 | | -28m-10=54 | | 7(3x/5)=11-(x/9) | | e^4x+3e^2x-18=0 | | 40x+.25y=50 | | -14m-12=79 | | cos^2(x)-sin^2(x)= | | 27y+12= | | 6x^6-9x^5-27x^4= | | 200.00+0.05s=75+0.10s | | 4x^4-4+x^3-x^2=0 | | 3x+10=5x-30 | | 24x^2+18x+5=0 | | X+34.01=44.8 | | 14+12=-15x+2 | | 3(2y-5)-2(y-4)= | | -5(10x+1*4)= | | (2lnx)(2x)= | | -1-5[4+2(c-3)]=2(c+1) | | 63-3x=33x+17 |